On the taxonomic validity of Pristimantis tepuiensis (Schlüter & Rödder, 2007) and P. stegolepis (Schlüter & Rödder, 2007), with remarks on the type series of P. guaiquinimensis (Schlüter & Rödder, 2007) - Kok, Philippe J.r.; Barrio-Amorós, César L. (Zootaxa, 2013)
The type series of Pristimantis guaiquinimensis (Schlüter & Rödder, 2007), P. tepuiensis (Schlüter & Rödder, 2007) and P. stegolepis (Schlüter & Rödder, 2007) have been thoroughly examined. We highlight a number of discrepancies in the original descriptions that do not support the recognition of P. stegolepis and P. tepuiensis as valid species. We demonstrate that P. stegolepis should be considered a junior synonym of P. vilarsi (Melin, 1941), and that P. tepuiensis should be considered a junior synonym of P. guaiquinimensis. We also point out that the sex of the holotype and paratype of P. guaiquinimensis have been wrongly determined.